Extracranial, peritoneal seeding of primary malignant brain tumors through ventriculo-peritoneal shunts in children: Case report and review of the literature. Issue 5 (October 2015) - Narayan, Anand; Jallo, George; Huisman, Thierry AGM
Introduction: Ventriculoperitoneal shunts (VPS) have been implicated as a source of the extraneural spread of a wide variety of central nervous system tumors. The purpose is to review the literature on peritoneal seeding of central nervous system tumors from VPS in the context of a case report. Methods: Medline was searched using the phrase 'peritoneal seeding ventriculoperitoneal shunt'. Inclusion criteria included patients (<18 years) with evidence of peritoneal seeding from VPS. Results: Search of the literature revealed a final total of 22 articles and a total of 28 patients. Case report: A 7-year-old boy presented with intermittent vomiting, headaches, photophobia; a 4.4 cm left thalamic mass (glioblastoma multiforme) was found. Occipital VPS catheters were placed for increasing hydrocephalus and the patient developed increased abdominal distention and pain. Computed tomography revealed diffuse ascites with carcinomatosis and the patient was diagnosed clinically with peritoneal metastases. Discussion: Our case report and literature review revealed 28 cases of central nervous system tumors demonstrating evidence of extraneural spread associated with VPS in children in a wide variety of tumors. Larger studies are required to evaluate VPS as potential risk factors for peritoneal seeding and familiarity with potential VPS-related peritoneal seeding is important for diagnostic consideration.